2010
DOI: 10.1016/j.otohns.2010.04.089
|View full text |Cite
|
Sign up to set email alerts
|

P65– Improving the quality of care of COPD patients in an internal medicine residency group by implementing the American Thoracic Society Guidelines

Abstract: A database was constructed that facilitated the development of multiple interfaces for varying professionals. Content management is streamlined from a centralized location, also ensuring consistency of guidelines between medical practitioners and case managers and claims adjustors. DISCUSSION (CONCLUSION): This study demonstrates that delivery of treatment guideline recommendations in a decision support system is an effective dissemination strategy that can be tailored to the needs of users not necessarily tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thirty-five studies reported on referral rates [3,7,; 28 of these were observational studies [3,7,[12][13][14][16][17][18][19][20][21][22][23][25][26][27][28][29][30][31][34][35][36][37][40][41][42]44], while the remaining seven assessed the effect of an intervention on COPD care (and measured referral rates at baseline and post-intervention) [15,24,32,33,38,39,43]. Nine studies reported on HCP perceived barriers to PR referral [23,26,[45][46][47][48][49][50][51], and seven of these also reported on enablers [23,26,45,…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-five studies reported on referral rates [3,7,; 28 of these were observational studies [3,7,[12][13][14][16][17][18][19][20][21][22][23][25][26][27][28][29][30][31][34][35][36][37][40][41][42]44], while the remaining seven assessed the effect of an intervention on COPD care (and measured referral rates at baseline and post-intervention) [15,24,32,33,38,39,43]. Nine studies reported on HCP perceived barriers to PR referral [23,26,[45][46][47][48][49][50][51], and seven of these also reported on enablers [23,26,45,…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…83% (n = 35) of included articles reported a referral rate to PR. In the observational studies (n = 28), referral rate ranged from 0% to 85% [3,7,[12][13][14][16][17][18][19][20][21][22][23][25][26][27][28][29][30][31][34][35][36][37][40][41][42]44] with a median referral rate of 17% (see Fig. 2).…”
Section: Referral Ratesmentioning
confidence: 99%